Daily actions, challenges, and needs among Dutch parents while supporting the participation of their child with a physical disability at home, at school, and in the community: a qualitative diary study. Issue 1 (December 2017) - Piškur, Barbara; Beurskens, Anna; Ketelaar, Marjolijn; Jongmans, Marian; Casparie, Barbara; Smeets, Rob
Abstract Background Parents have a vital influence on the participation of their child with a physical disability. The aim of this study is to gain insight into parents' own daily actions, challenges, and needs while supporting their child with a physical disability at home, at school, and in the community. An additional objective of this study is to refine the preliminary thematic framework previously identified in a scoping review. Methods A qualitative research inquiry was performed based on using a diary over a 7-day period to gather data. To systematically organise data into a structured format, content analysis has been applied using both inductive and deductive reasoning guided by the existing preliminary thematic framework. Results Analysis of the eligible diaries shows that the actions mentioned by the 47 parents describe several efforts to enhance participation of their children with a physical disability by using, enabling, or changing the social and physical environment, or by supporting their child to perform or engage in meaningful activities. Those parents' actions are primarily a result of challenges caused by restrictions in social and physical environments. Parental responses highlighted, above all, the need for environments designed for all people. Based on the findings a redefined thematic framework is presented. Conclusions Parents' actions, challenges, and needs are mainly directed towards the social or/and physical environment. The presented thematic framework can offer practitioners knowledge to support parents. More work is necessary to provide tailored approaches. Paediatric rehabilitation may need to address the importance of the environment on the participation of a child with a physical disability.